National identity of students of faculties of education in Serbia and Slovakia - Beljanski, Mila B.; Šimonji Černak, Ružena J.; Karikova, Sonja (Sociološki pregled, 2018)
The paper represents the research results of identifying the diﬀerences between the degree of national identity of the students of faulty of Education in Sombor and Banská Bystrica (Slovakia). National identity was measured with NAIT questionnaire (Scale of national identity) at the sample of 326 subjects of both genders and from both countries. Both groups of subjects have shown moderately expressed national identity. By factor analysis of the subjects we have extracted diﬀerent factors for both samples and the highest percentage of variance explains he factor relating to the sense of national identity. In both samples it has got diﬀerent content, especially form the standpoint of intensity of emotional association The results of this research have also shown that belonging to a particular nation supersedes belonging to humanity as a group